2012
DOI: 10.1175/jamc-d-11-0157.1
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of Drought Occurrences over Japan

Abstract: The drought climate of Japan from 1902 to 2009 was analyzed using an effective drought index (EDI). Drought regions were identified by hierarchical cluster analysis using drought characteristics (duration, severity, and onset and end dates) obtained from 50 observation stations. The results indicated that droughts could be divided into four groups (G1-G4) that reflected the local climate. The four groups were related to precipitation as follows. The summer rainy season affected groups G2-G4, in which droughts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Many other studies have also reported drought occurrences in the country [36][37][38]. Similar findings have been reported from North Korea [56][57][58], Japan [58], and China [59,60] that neighbor South Korea. There are also studies from other parts of the globe that have reported increased occurrences of droughts using SPI, SPEI, and SDI [61][62][63].…”
Section: Future Droughtsupporting
confidence: 82%
“…Many other studies have also reported drought occurrences in the country [36][37][38]. Similar findings have been reported from North Korea [56][57][58], Japan [58], and China [59,60] that neighbor South Korea. There are also studies from other parts of the globe that have reported increased occurrences of droughts using SPI, SPEI, and SDI [61][62][63].…”
Section: Future Droughtsupporting
confidence: 82%
“…Two decadal periods around the 1970s' and after the 1990s' deserve attention. Kim et al (2011) consider that extreme droughts during the stages of 1967-1969 and 1994-1996 are mainly caused by consecutive shortages of summer rainfall, the extreme event occurred in northern China, Japan and the Korean Peninsula (Lee et al 2012). …”
Section: Drought Charactermentioning
confidence: 99%
“…The EDI is a daily index that represents a continuous period and daily strength changes as objective values; it is an intensive measure that considers water accumulation with the weighting function of time passage. The merits of the EDI have been verified by many studies (Morid et al 2006;Pandey et al 2008;Lee and Byun 2009;Kim et al 2011;Lee et al 2012). The EDI is calculated using three equations:…”
Section: Introductionmentioning
confidence: 76%